IMPACT OF TECHNOLOGICAL ADVANCEMENTS ON ORGANIZATIONAL STRUCTURE AND OPERATIONS - M.PRADEEBA, B.NANDHINI (South Eastern European Journal of Public Health, 2025)
This study explores the profound impact of technological advancements on the organizational structure and operations of businesses in the contemporary era. As the pace of technological innovation accelerates, organizations worldwide are compelled to adapt to these changes to remain competitive and sustainable in a dynamic marketplace. The study employs a mixed-methods approach, integrating both qualitative and quantitative methodologies to comprehensively analyse the multifaceted effects of technology on organizational dynamics. A combination of surveys, interviews, and case studies were conducted across a diverse range of industries and company sizes to provide a nuanced understanding of the subject matter. The findings reveal several significant trends that indicate the transformational nature of technology in shaping organizational structures. First, the implementation of cutting-edge technologies has facilitated the decentralization of decision-making processes, leading to the emergence of flatter hierarchies and agile organizational structures. This shift has empowered employees at various levels to contribute ideas and innovate, fostering a culture of continuous improvement. Second, technological advancements have paved the way for greater flexibility in work arrangements, enabling remote work, flexible schedules, and virtual collaborations. This, in turn, has impacted workforce dynamics, leading to a more diverse and globalized workforce with implications for talent acquisition and retention strategies. The study highlights the role of artificial intelligence (AI), machine learning, and data analytics in enhancing operational efficiency and optimizing resource allocation. Automation of routine tasks has freed up human resources to focus on more strategic and creative aspects of their roles, driving innovation and value creation. The study discusses the challenges organizations face in adopting and integrating new technologies, such as cyber security risks, ethical concerns, and the need for up skilling the workforce to remain digitally competent.